Penetapan Ahli Waris Akibat Perkawinan Campuran Yang Belum Tercatatkan - Sa'adah, Nur; Widodo, Guntarto (Universitas Brawijaya, 2023)
The purpose of this study is to find out the case in case Number 762 K/Ag/2020, where the Panel of Judges upheld the decision of the High Court and rejected the ruling of the District Court. The considerations of the Panel of Judges are of the interpretation that a marriage will not have legal force if it is not registered, however, the nature of the registration is only administrative. This normative study examines the rule of law, legal principles, legal doctrine and the existing legal system in our country. It is important to examine the validity of mixed marriages that have not been recorded and the legal consequences of mixed marriages that have not been registered.